Accidental ingestion of 3% hydrogen peroxide in the neonatal period. Issue 1 (2nd January 2023) - Aydoğan, Seda; Fettah, Nurdan Dinlen; Akduman, Hasan; Zenciroğlu, Ayşegül
Abstract: Hydrogen peroxide (H2 O2) is an oxidizing agent. High concentrations of H2 O2 are used in the chemical industry, and 3% concentrations are used in household disinfectants. Severe H2 O2 toxicity occurs with a 35% concentration. After poisoning with H2 O2, corrosive damage occurs. We describe a 3-day-old male who ingested H2 O2 accidentally and was treated with supportive care. Hydrogen peroxide intoxication usually occurs in adults accidentally. This is the first report of a newborn case of H2 O2 ingestion.